2022
DOI: 10.47363/jjcmr/2022(2)132
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 Rich Proline are OPA1 Flux Influencer for PLCs and IFNs Synthesis where Immune and Toxicity Due Deficiency in Synthetase and in Proline Synthesis

Abstract: Rac1 is basis for ATPase, ribosomes repairs, Gactin activities, and regulating fatty Acyl-COA productions (upon OPA1 function) which are main for epidermal growth factor “EGF” synthesis and for both PLCs and IFNs synthesis. Rac1 basically are S6K rich Proline and hydrophobic amino acids that each amino acid especially Proline characterize Rac1 for scpsific functions and activity for regulating specific anti-inflammatory cycles and specific anti-inflammatory growth, that Rac1 has the roles of acting on inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Rac1 are so necessary for regulating IFN-beta and PLCγ2 which necessary for TXA2 synthesis and platelet activation where, fibrin imp for activating CMs and endothelial cells: That PLCγ2 has necessary functions for regulating TXA2 and reactivating platelets [10].…”
Section: Introduction and Methodsmentioning
confidence: 99%
“…Rac1 are so necessary for regulating IFN-beta and PLCγ2 which necessary for TXA2 synthesis and platelet activation where, fibrin imp for activating CMs and endothelial cells: That PLCγ2 has necessary functions for regulating TXA2 and reactivating platelets [10].…”
Section: Introduction and Methodsmentioning
confidence: 99%
“…And, previous studies indicate that 5-HT stimulated angiogenesis through activation of Akt in ECs [90]. And, Serotonin/5-HT1A Signaling in the Neurovascular Unit Regulates Endothelial CLDN5 Expression and, serotonin 5-HT regulates the balance of Th17/Tregs and promotes M2-polarization of macrophages and has a direct or indirect regulatory effect on traditional immunocytes such as T cells, macrophages, DC cells, and NK cells [91,92].…”
Section: The Role Of Serotonin In Activating T-cells and Promotingmentioning
confidence: 97%
“…Where, studies reported that: Deficiency in pyrimidine kinases cause cholesterol accumulation and increase the risk of coronary artery disease [45].…”
Section: Figurementioning
confidence: 99%